IT-Risikomanagement von Cloud-Services in Kritischen Infrastrukturen : HMD Best Paper Award 2017 /: HMD Best Paper Award 2017. ([2018]) - Adelmeyer, Michael; Petrick, Christopher; Teuteberg, Frank, 1970-
No abstract available